THE INFLUENCE OF COMPETENCE AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE AT THE DARMASRAYA REGENCY CULTURE AND TOURISM OFFICE - Lubis, Donly Wance; Winanda, Vanny Nuari; Aima, M. Havidz; Ridwan, Ridwan (Gapenas Publisher, 2025)
The purpose of this study is to find out and analyze the competencies, career development, work discipline, and performance of employees at the Darmasraya Regency Culture and Tourism Office. The method and type of research used is a type of quantitative research with a survey research method, data was obtained directly through questionnaires to 48 respondents who were employees at the Darmasraya Regency Education and Culture Office. Sample extraction uses the overall sampling technique (total sampling). Data analysis was carried out in several stages, namely 1) Validity Test was tested with Pearson correlation (r count > r table). 2) Reliability tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality Test to find out whether the data is normally distributed or not 4) T test to find out the influence of each independent variable on the dependent variable. 5) F test to determine the influence of competency and career development simultaneously on employee performance. 6) Coefficient of Determination (R²) to find out how much contribution independent variables contribute in explaining dependent variables. Based on the results of the research and discussion that has been stated above, several conclusions can be drawn as follows: 1)Competency variables affect the performance of employees at the Darmasraya Regency Culture and Tourism Office. This means that the better the competence, the higher the level of performance. 2) Career Development variables have a positive effect on the performance of employees at the Darmasraya Regency Culture and Tourism Office. This means that the better the work discipline of employees across the agency, the more employee performance will increase. 3) Simultaneously Competence, and Career Development have a positive effect on the performance of employees at the Darmasraya Regency Culture and Tourism Office.